Open-comminuted mid humeral fracture in a long-tailed macaque (Macaca fascicularis) – case report - Abdullah, Abraham Gabriel; Boo, Ao Lin; Mohamad Yusof, Loqman (Department of Wildlife and National Parks (DWNP) Peninsular Malaysia, 2018)
A 2-year-old long-tailed macaque (Macaca fascicularis) was presented to the University Veterinary Hospital, Universiti Putra Malaysia for a traumatic injury to the left arm. Physical examination findings revealed a lacerated wound of 2 cm x 1 cm with distal humeral bone segment was protruding out from the muscles and skin. There were delayed pain sensation and withdrawal reflex of the left upper arm. Radiographic findings revealed discontinuity of the left humerus at the mid-shaft with a single fragment from the distal segment at the fracture site. The fracture was repaired with an open reduction and fixation technique with a combination of intramedullary pinning and cerclage wire. The patient regained motor function of the arm after six weeks of intramedullary pin implantation. Here we describe the severity of each grading system and the principles of open fracture management in macaques.